Analisis Pelaksanaan Asesmen Kompetensi Madrasah Indonesia (AKMI) - Susanti, Lisa Dwi; Pahrudin, Agus; Yetri (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
Student management cannot be separated from student evaluation activities. The Indonesian Madrasah Competency Assessment (AKMI) is the latest program owned by the Ministry of Religious Affairs of the Republic of Indonesia, where AKMI is one of the evaluation tools for students. This study aims to analyze the implementation of AKMI at the State Ibtidaiyah Madrasah in Bandar Lampung City, whether all parties involved have carried out standard operating procedures (POS) for the implementation of AKMI in 2021 in accordance with applicable regulations. This research is a qualitative research with an analytical approach to find out more about how the implementation of AKMI in Kota Bandar Lampung , namely by describing the existing facts. The research was carried out by triangulation of data collection techniques, namely interviews, observations and documentation. In this study, the researcher conducted an interview with the section head and implementer of the curriculum development in the field of madrasah education of the Ministry of Religion Kota Bandar Lampung, then with the head of the madarash, proctors, technicians, teachers, and participants of the assessment test at MIN 1, MIN 9 and MIN 10 Bandar Lampung. The results of the study showed that the AKMI test can provide a clear diagnosis of the students' abilities. Meanwhile, regarding the implementation of AKMI, the duties and responsibilities carried out by the Ministry of Religion of Bandar Lampung City and the Ibtidaiyah Negeri Madrasah whose implementation is based on the POS for the implementation of the 2021 AKMI have been implemented very well. Furthermore, the preparation of the AKMI-BK system in MIN 1, MIN 9 and MIN 10 Bandar Lampung which includes the preparation of local servers, clients, LAN networks, system installations, and application installations, ensures that the use of computers is in accordance with existing regulations. The last is about the assessment results of test takers related to their abilities in the fields of reading literacy, numeracy literacy, science literacy, and socio-cultural literacy where the results obtained show that the test takers' abilities are mostly at a very low level.